Fabrication of Patterned Integrated Electrochemical Sensors. (5th August 2015) - Mujeeb-U-Rahman, Muhammad; Adalian, Dvin; Scherer, Axel
Abstract : Fabrication of integrated electrochemical sensors is an important step towards realizing fully integrated and truly wireless platforms for many local, real-time sensing applications. Micro/nanoscale patterning of small area electrochemical sensor surfaces enhances the sensor performance to overcome the limitations resulting from their small surface area and thus is the key to the successful miniaturization of integrated platforms. We have demonstrated the microfabrication of electrochemical sensors utilizing top-down lithography and etching techniques on silicon and CMOS substrates. This choice of fabrication avoids the need of bottom-up techniques that are not compatible with established methods for fabricating electronics (e.g., CMOS) which form the industrial basis of most integrated microsystems. We present the results of applying microfabricated sensors to various measurement problems, with special attention to their use for continuous DNA and glucose sensing. Our results demonstrate the advantages of using micro- and nanofabrication techniques for the miniaturization and optimization of modern sensing platforms that employ well-established electronic measurement techniques.